Evaluation of targeted therapy on the activity of curcumin and doxorubicin anticancer agents in breast cancer: A systematic literature review - Indriani Dwi Kartika; Dewi Salma Kumala; Az-zahra Mutiara; Siagian Dina Ariya; Alifatunnisa Nur Iqlima; Lolita Lolita; Novitasari Putri Rachma; Ittiqo Dzun Haryadi; Ikhsanudin Azis (BIO Web of Conferences)
Breast cancer is one type of cancer that causes the most deaths in women. Currently, doxorubicin chemotherapy treatment is widely used, but due to untargeted side effects, a hydrogel-thermosensitive preparation has been developed by comparing the activity of the active substance curcumin with doxorubicin. This systematic review aims to determine the development of research on the anticancer activity of modified hydrogel-thermosensitive breast cancer and to examine its activity by looking at the IC50 value. The method used in searching for articles was using the Scopus database with the type of literature analyzed, namely research on the cytotoxic activity of curcumin and doxorubicin with key keywords (“Doxorubicin” OR “Curcumin” AND “Breast” AND “Cancer” AND “Therapy” AND “ Cytotoxicity”). The inclusion criteria used were journals containing cytotoxic or anti-breast cancer tests from curcumin and doxorubicin with publication years 2020-2024, and full-text journals. The exclusion criteria used were journals that did not test cytotoxicity on MCF-7 cells, no IC50 value, journals regarding review articles, and paid journals. The analysis results show that curcumin has an IC50 value comparable to doxorubicin with the mechanism of inducing apoptosis in cancer cells by activating caspase 3 and caspase 9. So the development of a thermosensitive hydrogel provides an opportunity for the anticancer activity provided to be more targeted.